1983
DOI: 10.1515/cclm.1983.21.5.273
|View full text |Cite
|
Sign up to set email alerts
|

The Protein-Bound Carbohydrates of Seromucoid from Normal Human Serum

Abstract: The neutral sugars and hcxosamines in the seromucoid fraction of normal human serum were identified and determined simultaneously by gas-liquid chromatography of their aldononitrilc acctates. Besidcs the sialic acid, normal seromucoid contained fucose, arabinose, mannosc, glucose, galactose, glucosamine and galactosamine. The presence of arabinose and glucose, not previously reported in seromucoid, äs well äs the other known carbohydrate components determined by GLC were confirmed from their fragmentation patt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

1991
1991
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 15 publications
(12 reference statements)
0
10
0
Order By: Relevance
“…Therefore, the high content of fucose and galactose could derive from the carbohydrate moiety of mucins. At the same time it was reported that the seromucoid fraction of human serum contained fucose, arabinose, mannose, glucose, galactose, glucosamine and galactosamine [36]. Rhamnose was not reported to be a component of the macromolecules mentioned above and therefore it is reasonable to correlate its presence with that of cepacian.…”
Section: Discussionmentioning
confidence: 97%
“…Therefore, the high content of fucose and galactose could derive from the carbohydrate moiety of mucins. At the same time it was reported that the seromucoid fraction of human serum contained fucose, arabinose, mannose, glucose, galactose, glucosamine and galactosamine [36]. Rhamnose was not reported to be a component of the macromolecules mentioned above and therefore it is reasonable to correlate its presence with that of cepacian.…”
Section: Discussionmentioning
confidence: 97%
“…Evaluation of the TSA concentration may be useful for diagnosing inflammatory diseases due to the increase in sialic acid during the inflammatory process, such as tissue degeneration and proliferation ( Singh and others 1980 , Haq and others 1993 , Citil and others 2004 ). Varma and others (1983) studied the protein-bound carbohydrates of seromucoid in normal human serum and reported that many acute phase proteins contain sialic acid. Due to acute phase proteins in the form of glycoprotein, an increase in these proteins in circulation affects the serum TSA level ( Taniuchi and others 1981 ).…”
Section: Discussionmentioning
confidence: 99%
“…This hypothesis is supported by the investigations on sialylated glycoproteins in serum. Some of the sialylated glycoproteins rapidly increase in response to the onset of inflammation and are regarded as an index of acute phase response [ 27 ].…”
Section: Biological Functions Of Albuminmentioning
confidence: 99%